The Effectiveness of Power Point-Assisted Picture Books on Receptive Language Development in Early Childhood - Ariyanto, Fajar; Tanto, Octavian Dwi (Jurnal Pendidikan Anak, 2021)
This study aims to determine the interests of children from the use of picture storybooks assisted by the Microsoft PowerPoint application in the development of receptive language in early childhood with a research focus on the ability to listen to simple stories. The type of research used is descriptive with a quantitative approach. The data collection technique used in this study was a questionnaire with a Likert scale of 4, where the answer choices were on each question item. The number of questionnaire items used in this study amounted to 6 questions. The results of this study indicate that there are various responses about the impact of using picture storybooks. First, about the difficulty of applying online storybook media too early childhood, the results are 71.4% relatively easy to use, second, children's interest in listening to stories using the PowerPoint application results in 54% of children being very interested, the three PowerPoint applications being an alternative to PAUD learning today. Getting 38.1% results is quite alternative, the four stimulations of early childhood development can be given through impressions on the PowerPoint screen getting 60.3% results can be stimulated, the five children feel unfamiliar with the technology used to get 66.7% results do not feel foreign Regarding the media used, the six obstacles in learning to use PowerPoint media got results 66.7% answered that they did not experience problems in the implementation of storytelling using the powerpoint application.